Public Participation in the Law-Making in the Digitalization Era - Dodi Jaya Wardana; Hasnan Bachtiar (Universitas Muhammadiyah Malang, 2022)
Technology can play an important role and provide a useful tool for creating informed and active citizens, thereby contributing to democracy from the ground up. The shift from e-governance to e-democracy has become an important example of the capacity of technology to influence public law as a whole. There are at least four methods that can be used to participate in public participation in law-making, namely digitally: Interactive Applications, Legislative Crowdsourcing, and Utilizing Big Data. There are at least 2 (two) ways that the community can conventionally take to get involved in forming the law, namely active participation, and passive participation. Through active participation, the public takes the initiative to participate in the process of forming legislation products by attending general meetings, and public debates, as well as writing open letters in the mass media addressed to the apparatus in charge of discussing the Draft Law. Passive participation means that participation initiatives come from outside the community.